2020
DOI: 10.1111/ggi.14102
|View full text |Cite
|
Sign up to set email alerts
|

COVID‐19 in older adults: What are the differences with younger patients?

Abstract: Aim The present study aimed both to gain knowledge on the distinctive clinical characteristics of older adults with coronavirus disease 2019 (COVID‐19), in comparison with those of younger patients, and to identify risk factors for mortality. Methods A retrospective observational study was carried out of patients consecutively admitted to Doctor Peset University Hospital, Valencia (Spain) for COVID‐19 from 11 March to 28 April 2020. Every case was diagnosed by reverse t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(50 citation statements)
references
References 28 publications
1
44
0
2
Order By: Relevance
“…The differences in feature relevance could also be explained by the small number of people in the age groups used, specifically older people who might be less prone to register their symptoms regularly, and fewer evident and aggressive symptoms in younger participants than in older participants. 24,25 Therefore, future research should focus on the development of submodels targeting the specificities of the age subgroups that showed signifi cantly different features. Nevertheless, the prediction of COVID-19 diagnosis across all the age groups had a consistently high certainty.…”
Section: Discussionmentioning
confidence: 99%
“…The differences in feature relevance could also be explained by the small number of people in the age groups used, specifically older people who might be less prone to register their symptoms regularly, and fewer evident and aggressive symptoms in younger participants than in older participants. 24,25 Therefore, future research should focus on the development of submodels targeting the specificities of the age subgroups that showed signifi cantly different features. Nevertheless, the prediction of COVID-19 diagnosis across all the age groups had a consistently high certainty.…”
Section: Discussionmentioning
confidence: 99%
“…We did not observe any difference between men and women for the same assay but did observe a difference between individuals aged less or more than 65 years and those hospitalized or not for COVID-19. These two criteria are strongly linked, as a greater proportion of people over 65 years old are hospitalized for COVID-19 [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…The overall mortality rate in this study was 8.1% (26), while 72.9% (234) of the patients remained in the ICU for 1-6 days. Each patient was infected with one type of bacteria or fungi; presented as respiratory infection, bacteremia, and skin infections.…”
Section: Resultsmentioning
confidence: 57%
“…Numerous investigations found that older COVID-19 patients aged ≥ 50 years were correlated with higher risk for severe signs, atypical presentation, the opportunity for co-infections and higher fatality rates compared to patients with <50 years of age, and the rate usually increases rapidly with age; it is not surprising due to the drop in natural immunity by age, associated comorbidities and it is believed that older people are prone to adverse drug reactions. In general, people of different ages are prone to get infected with the COVID virus (25) (26). A review reported a twice higher fatality rate in males compared to females; it has stated that male patients may have higher ACE-2 enzyme activity, directed by male sex hormones, contributing to more risk for SARS-CoV-2 infection and worsening clinical outcomes (27).…”
Section: Discussionmentioning
confidence: 99%